2023
DOI: 10.47307/gmc.2023.131.s1.9
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the incidence of premature rupture of membranes in Probolinggo District

Abstract: Introduction: Premature rupture of membranes (PROM) is the rupture of the amniotic membranes before there are signs of labour. Objective: This Study aims to analyze the factors that influence the premature rupture of membranes. Methods: This research is analytic research with a cross-sectional design. The research was conducted in Probolinggo Regency. The population is all mothers giving birth in Probolinggo Regency in June – August 2021 as many as 90 people. The sampling technique uses total sampling. Sample:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…The results of bivariate analysis in this study show a p-value of 0.150>α (0.05), so it can be concluded that there is no significant relationship between multiple pregnancies and the incidence of premature rupture of membranes in preterm pregnancies. This is consistent with a study conducted by Zakiyyah et al entitled Factors influencing the incidence of premature rupture of membranes in Probolinggo District, East Java, Indonesia, which states that there is no relationship between twin pregnancies and the incidence of premature rupture of membranes with a p-value of 0.435 [31].…”
supporting
confidence: 92%
“…The results of bivariate analysis in this study show a p-value of 0.150>α (0.05), so it can be concluded that there is no significant relationship between multiple pregnancies and the incidence of premature rupture of membranes in preterm pregnancies. This is consistent with a study conducted by Zakiyyah et al entitled Factors influencing the incidence of premature rupture of membranes in Probolinggo District, East Java, Indonesia, which states that there is no relationship between twin pregnancies and the incidence of premature rupture of membranes with a p-value of 0.435 [31].…”
supporting
confidence: 92%